Implementasi Metode TOPSIS Untuk Menentukan Dosen Terbaik (Studi Kasus : STMIK Bina Nusantara Jaya Lubuklinggau) - Yayang Eluis Bali Mawartika; Arie Yandi Saputra (STMIK Bina Nusantara Jaya Lubuk Linggau, 2024)
STMIK Bina Nusantara Jaya Lubuklinggau is one of the universities in Lubuklinggau which was founded in 2007. Currently there are 20 permanent lecturers. At the higher education level, lecturers are professional staff who are appointed through statutory regulations. As teaching staff, lecturers have an obligation to provide knowledge to students in higher education. As an effort to support the teaching and learning process on campus, selection of the best lecturers is often held directly by students. However, the process of selecting the best lecturer still has shortcomings, namely that students only choose their favorite lecturer without looking at the teaching and learning process provided by the lecturer. Therefore, this research will implement decision support methods to help make more accurate decisions in determining the best lecturer. The method implemented in the decision support system for determining the best lecturers is the TOPSIS method. There are 6 criteria used to determine the best lecturers, namely length of service, achievements, semester learning plans, teaching materials, learning media, and lecturer presence. Based on the calculation results of the implementation of the TOPSIS method on 5 lecturers who have been certified, Robi Yanto is the best lecturer with the highest score, namely 0,86.